PROSPECTS FOR DEVELOPMENT OF MANAGEMENT AUTHORITY AND COMPETENCES OF LEADING PERSONNEL - Xusanov Azimjon Nozimjonovich (American Journals, 2024)
This article discusses the role and importance of management personnel in management processes, leadership potential and competencies, as well as their specific characteristics, and also provides individual recommendations based on the findings. The prospects for the development of management potential and competencies of management personnel in our country were also explained.
Keywords: Leader, leader image, leadership potential, AIDA, charisma, competence, quality, leadership style, competence, leader.